"Sous Les Pavés, Le Gitan, " Or a Romani Counter-Narrative to May 1968. Issue 2 (15th March 2019) - Chirila, Ileana D.
Abstract: Although it occurred mostly during the same period as the revolts of May 1968, and it was hugely consequential for the Roma social movement, the "Romani revolution" is generally absent from French textbooks. This article describes the events that occurred during those years, and the groundwork of diverse Romani activists that led to the emergence of collective structures of representation.